Karakteristik Perkembangan Anak Usia 4 Tahun - Ramadan Lubis; Dicky Chandra Lubis; Muhammad Falih Daffa; Namira Sazkia; Pramudia Ananda; Rizka Rahman Tanjung; Windi Melisa (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to examine the development of 4-year-old children, with a focus on physical, cognitive, emotional, spiritual, and social aspects. The research method used is qualitative with a descriptive approach, which focuses on understanding phenomena through interviews, observations, and documentation. The subject of the study was a child named Kennan Rafardhan, who was 4 years old and lived in Medan. Data collection techniques are carried out through interviews with parents, direct observation, and documentation related to child development. Data analysis follows the steps of data collection, data reduction, and conclusion assertion. The results showed that Kennan's physical development was in the normal range with a height of 120 cm and a weight of 23 kg, higher than the average child of his age. In the cognitive aspect, Kennan has shown reading and memorization skills, although pronunciation and reading comprehension need further improvement. In the emotional aspect, he showed the ability to control anger and manage feelings of disappointment, as well as begin to understand jealousy. In spiritual development, Kennan shows interest and awareness of religious practices, such as prayer and recitation, as well as memorization of daily prayers. On the social side, he is able to get along with his friends, understand social norms, and show empathy for others. Overall, this study found that Kennan Rafardhan's development showed significant progress in all aspects studied, according to the age and stage of child development in general. This research provides an important overview of early childhood development, which can be used as a reference for parents and educators in supporting children's growth and development.